1995
DOI: 10.1177/0022427895032002003
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality and Rates of Female Homicide Victimization Across U.S. Cities

Abstract: This study adds to a growing body of literature that explores patterns and correlates of homicide among specific populations within the United States. Seeking to improve our understanding of correlates of female homicide, the authors explore the possibility that female victimization rates are influenced by conditions of sex-based inequality. Using data from 177 central cities of the United States, they develop a model that tests separately, and in combination, the effects of seven sociodemographic variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
6
45
0
1
Order By: Relevance
“…This backlash hypothesis stressed an unintended consequence of female empowerment: increased gender equality represented a threat to male dominance and might result in higher rates of female victimization as males react defensively (Messerschmidt, 1993). This approach (Russell, 1975;Williams & Holmes, 1981) was similar to Blalock's threat hypothesis (1967) and also received some empirical support, with Bailey (1999), Brewer and Smith (1995), Vieraitis and Williams (2002), and Whaley (2001) showing a positive relationship between selected measures of gender equality and rape or female homicide victimization.…”
Section: Previous Literaturementioning
confidence: 84%
“…This backlash hypothesis stressed an unintended consequence of female empowerment: increased gender equality represented a threat to male dominance and might result in higher rates of female victimization as males react defensively (Messerschmidt, 1993). This approach (Russell, 1975;Williams & Holmes, 1981) was similar to Blalock's threat hypothesis (1967) and also received some empirical support, with Bailey (1999), Brewer and Smith (1995), Vieraitis and Williams (2002), and Whaley (2001) showing a positive relationship between selected measures of gender equality and rape or female homicide victimization.…”
Section: Previous Literaturementioning
confidence: 84%
“…Research also showed that macrosocial variables (e.g., levels of poverty and unemployment, racial income gaps, divorce rates, occupational inequalities, etc.) could impact rates of sexual assault and homicide (see Baron & Straus, 1989;Brewer & Smith, 1995;Peterson & Bailey, 1988, 1992Smith & Bennett, 1985), as well as general sentencing and imprisonment practices (Michalowski & Pearson, 1990;Myers & Talarico, 1986). Future research should attempt to specify race effects within hierarchical models that can account for organizational and contextual variations across different jurisdictions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Homicide [8] studies employing gender stratification as the explanatory framework are typically concerned with the victimization of women. Yet gender inequality theories are useful in uncovering the structural dynamics that underlie child homicide victimization as well.…”
Section: Theoretical Perspectivementioning
confidence: 99%